## Solving the Equation: (x - 4/5)(x + 2 1/5) = 0

This equation is a quadratic equation in factored form. To solve for *x*, we can use the **Zero Product Property**, which states that if the product of two factors is zero, then at least one of the factors must be zero.

**1. Identify the factors:**

The equation is already factored for us: (x - 4/5) and (x + 2 1/5) are the two factors.

**2. Set each factor equal to zero:**

- x - 4/5 = 0
- x + 2 1/5 = 0

**3. Solve for x in each equation:**

- x = 4/5
- x = -2 1/5

**Therefore, the solutions to the equation (x - 4/5)(x + 2 1/5) = 0 are x = 4/5 and x = -2 1/5.**

**Explanation:**

This equation represents a parabola intersecting the x-axis at two points. These points correspond to the solutions we found, x = 4/5 and x = -2 1/5. The factored form of the equation highlights the x-intercepts, making it easier to find the solutions.